Structural complexity in the boundary of forearc basin – accretionary wedge in the northwesternmost Sunda active margin - Maruf M. Mukti (BULLETIN OF THE MARINE GEOLOGY, 2018)
The area from Andaman to northern Sumatran margin is a region where major faults collided that complicates the structural configuration. The origin of structures in the boundary between the accretionary wedge and forearc basin in the northwesternmost segment of the Sunda margin has been a subject of debates. This article reviews several published works on the Andaman – north Sumatran margin to characterize the boundary between forearc basin and accretionary wedge. Complex strain partitioning in this margin is characterized by sliver faults that crossing boundaries between the backarc basin, volcanic arc, forearc basin, and accretionary wedge. The fault zone can be divided into two segments: The West Andaman Fault (WAF) in the north and Simeulue Fault (SiF) in the southern part. A restraining step-over formed in between WAF and SiF. The SiF may extent onshore Simeulue to a strike-slip fault onshore. Strain-partitioning in such an oblique convergent margin appears to have formed a new deformation zone rather than reactivated the major rheological boundary in between the accretionary wedge and forearc basin. The eastern margin of the Andaman-north Sumatra accretionary wedge appears to have form as landward-vergent backthrusts of Diligent Fault (DF) and Nicobar Aceh Fault (NAF) rather than strike-slip faults. This characteristic appears to have formed in the similar way with the compressional structures dominated the eastern margin accretionary wedge of the central and south Sumatra forearc. Keywords: Andaman, North Sumatra, forearc, structure, accretionary wedge, strain partitioningDaerah Andaman - Sumatera bagian utara adalah wilayah di mana patahan-patahan besar saling bertemu dan membuat konfigurasi struktur menjadi rumit. Asal-usul struktur di batas antara prisma akresi dan cekungan busur muka di bagian paling baratlaut dari tepian Sunda telah menjadi topik perdebatan. Artikel ini mengulas beberapa studi yang telah diterbitkan sebelumnya mengenai tepian Andaman - Sumatra bagian utara untuk mengkarakterisasikan batas antara cekungan muka dan prisma akresi. Pemisahan regangan yang kompleks di tepian ini dicirikan oleh sliver fault yang melintasi batas antara cekungan busur belakang, busur vulkanik, cekungan busur muka, dan prisma akresi. Zona sesar tersebut dapat dibagi menjadi dua segmen, yaitu Sesar Andaman Barat (WAF) di utara dan Simeulue Fault (SiF) di bagian selatan. Sebuah restraining step-over terbentuk di antara WAF dan SiF. SiF kemungkinan menerus sampai ke Pulau Simeulue dan menyatu dengan sesar geser. Pemisahan regangan di tepian konvergen yang miring seperti itu tampaknya telah membentuk zona deformasi baru daripada mengaktifkan kembali batas reologi utama di antara prisma akresi dan cekungan busur muka. Batas bagian timur dari prisma akresi di Andaman – Sumatera bagian utara memiliki bentuk sebagai backthrusts berarah darat yaitu Sesar Diligent (DF) dan Sesar Nicobar Aceh (NAF) dan bukan merupakan sesar geser. Karakteristik ini tampaknya terbentuk dengan proses yang mirip dengan struktur-struktur kompresional yang mendominasi bagian timur prisma akresi di daerah Sumatra bagian tengah dan selatan.Kata kunci: Andaman, Sumatera bagian, busur muka, struktur, prisma akresi, pemisahan regangan